Creative production and existential thought: a feminist existential analysis of South African visual artist Berni Searle's artwork - Mokwena, Palesa (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
Through an analysis of the work of South African artist Berni Searle, my study will investigate feminist existential ideas and concepts that have been explored by various creative producers in and outside of Europe/South Africa through different forms of creative productions and under different epistemological categories. 'Canons' of European existentialist/feminist thought often exclude the existence of feminist existential knowledge productions and producers outside of Europe. In conducting this study, I am responding to the past and present separatist and identitarian categorisations of creative productions from black/African creative producers, particularly women creative producers in South Africa, creating an alternative canonisation around their selected works. Although canons have been and can be used to drive separatist and identitarian categorisations, it is my hope to elucidate a discourse around the preservations and acknowledgements of South African creative and knowledge productions through a feminist existential framework that canonises important black feminist existentialist works and thereby brings to light their intellectual contributions over and above their identities. My development of a South African feminist existentialism is an attempt to graft a more intersectional, holistic framework to introduce in the feminist and existential discourses, and to proffer a new intersectional holistic paradigm of discussing categories that do not limit creative productions. To frame this research, I will reflect on the politics of historical and contemporary South African society as it is reflected in the works of the chosen creative producers and theorists and to question how we respond as creative feminist existentialists to contemporary South African struggles and how such a lens can be activated as a creative-theoretical tool of investigation.
Keywords: Women artists -- South Africa; Women artists, Black -- South Africa; Existentialism and art; Feminism and art -- South Africa; Searle, Berni